Mufassir's Differences in Opinion on Understanding the Verses of Dhikr in the Qur'an - Fuji Fauziah Nurul Aisyah; Agus Sopian (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to discuss differences of opinion among commentators regarding the understanding of the verses of remembrance in the Koran. This research method is a qualitative type through literature study with content analysis. The results and discussion of this study include the meaning of remembrance, the variety of verses of remembrance in the Koran, and differences of opinion among mufassirs about the verses of remembrance. The conclusion of this study is that the differences of opinion among commentators in understanding the verses of this remembrance, namely in terms of their application, are part of the varied differences that do not deny each other the understanding of other scholars and are not contradictory. This understanding is viewed from the perspective of classical commentators. This study recommends that interpretation research be carried out among contemporary modern commentators whose sources of interpretation are in the form of a combination of bi al-Ra'yi and bi al-Ma'tsur regarding the understanding of these remembrance verses in terms of their application.